THE EVALUATION ON THE FINANCIAL PERFORMANCE OF PAPER AND PULP COMPANIES IN INDONESIA - Rinaldi Syahran; Dedi Budiman Hakim; Dadang Sukandar (School of Business, IPB University (SB-IPB), 2016)
In 2013, the government has made the pulps and papers industries into a strategic sector. The decision to make the pulp and papers as the strategic sector, proved that the government is serious in developing companies in this sector. However, in the same year the producer’s margin in the Asia market has dropped. Hence, due to the two reasons, the financial performance of the Pulps and Papers in Indonesia need to be evaluated. The objective of the research is to evaluate the financial performance of the pulps and papers companies in Indonesia. The method is using the financial ratio and economic value added that is obtained from the financial data report. The data are entered and processed using Excel software. The result obtained is that in a long term, the Tjiwi Kimia paper company has the best financial performance in solvability and profitability, while Indah Kiat Pulps and Papers Company have the best long term liquidity. In a long term, there are no companies have the best economic value added. In 2013, Indah Kiat Pulps and Papers have the best financial performance in terms of liquidity, profitability and economic value added production, while Tjiwi Kimia Company has the best solvability. Keywords: economic value added, financial performance evaluation, pulp and papers, financial ratio, financial report